Bempedoic acid: effects on lipoprotein metabolism and atherosclerosis. Issue 1 (February 2019) - Burke, Amy C.; Telford, Dawn E.; Huff, Murray W.
Abstract : Purpose of review: Bempedoic acid has emerged as a potent inhibitor of ATP-citrate lyase (ACLY), a target for the reduction of LDL cholesterol (LDL-C). We review the impact of bempedoic acid treatment on lipoprotein metabolism and atherosclerosis in preclinical models and patients with hypercholesterolemia. Recent findings: The liver-specific activation of bempedoic acid inhibits ACLY, a key enzyme linking glucose catabolism to lipogenesis by catalyzing the formation of acetyl-CoA from mitochondrial-derived citrate for de novo synthesis of fatty acids and cholesterol. Adenosine monophosphate-activated protein kinase activation by bempedoic acid is not required for its lipid-regulating effects in vivo . Mendelian randomization of large human study cohorts has validated ACLY inhibition as a target for LDL-C lowering and atheroprotection. In rodents, bempedoic acid decreases plasma cholesterol and triglycerides, and prevents hepatic steatosis. In apolipoprotein E-deficient ( Apoe −/− ) mice, LDL receptor-deficient ( Ldlr −/− ) mice and LDLR-deficient miniature pigs, bempedoic acid reduces LDL-C and attenuates atherosclerosis. LDLR expression and activity are increased in primary human hepatocytes and in Apoe −/− mouse liver treated with bempedoic acid suggesting a mechanism for LDL-C lowering, although additional pathways are likely involved. Phase 2 and 3 clinical trials revealed that bempedoic acid effectively lowers LDL-C as monotherapy, combined with ezetimibe, added to statin therapy and in statin-intolerant hypercholesterolemic patients. Treatment does not affect plasma concentrations of triglyceride or other lipoproteins. Summary: The LDL-C-lowering and attenuated atherosclerosis in animal models and reduced LDL-C in hypercholesterolemic patients has validated ACLY inhibition as a therapeutic strategy. Positive results from phase 3 long-term cardiovascular outcome trials in high-risk patients are required for bempedoic acid to be approved for prevention of atherosclerosis.